Electrically conductive hybrid organic crystals as flexible optical waveguides - Xuesong Yang; Linfeng Lan; Xiuhong Pan; Xiaokong Liu; Yilong Song; Xueying Yang; Qingfeng Dong; Liang Li; Panče Naumov; Hongyu Zhang (Nature Communications, 2022)
The poor conductivity of organic crystals hinders their potential on applications in flexible electronics, wearable devices, and soft robotics. Here, Naumov et al. develop a hybrid organic crystal that shows enhanced electrical conductivity and fast mechanical deformation due to temperature change.